1992
DOI: 10.1099/0022-1317-73-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of woodchuck hepatitis virus infection of peripheral blood mononuclear cells by flow cytometry and polymerase chain reaction

Abstract: Peripheral blood mononuclear cells (PBMCs) from 10 woodchuck hepatitis virus (WHV)-infected woodchucks were examined for the presence of WHV surface (WHs) and core (WHc) antigens (WHsAg and WHcAg) by cytofluorometry using fluorescein isothiocyanate-conjugated anti-WHs and anti-HBc-purified immunoglobulins from woodchuck and human sera. The presence of viral DNA and RNA was detected in the serum and PBMCs from the same blood samples by polymerase chain reaction (PCR) with two primer sets located in the S and C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…WHV DNA and RNA have been identified in PBMCs and lymphatic organs of woodchucks with WHsAg-reactive chronic hepatitis (29,30) and in convalescent animals shortly after seroconversion to anti-WHs (31). In our laboratory, pathogenic virus has been documented in lymphoid cells throughout the life-span of woodchucks after apparent complete recovery from AH (19).…”
Section: Discussionmentioning
confidence: 99%
“…WHV DNA and RNA have been identified in PBMCs and lymphatic organs of woodchucks with WHsAg-reactive chronic hepatitis (29,30) and in convalescent animals shortly after seroconversion to anti-WHs (31). In our laboratory, pathogenic virus has been documented in lymphoid cells throughout the life-span of woodchucks after apparent complete recovery from AH (19).…”
Section: Discussionmentioning
confidence: 99%
“…In another work, Chemin et al demonstrated the selective detection of HBsAg and HBcAg on B lymphocytes and natural killer cells from chronically HBV-infected patients (52). Hepatitis C virus (HCV), woodchuck hepatitis virus, and varicella-zoster virus were also detected by FCM in PBMCs using monoclonal antibodies to HCV core antigen (34), polyclonal antibodies to woodchuck hepatitis virus (51), and antibodies to the gpI glycoprotein from varicella-zoster virus (296), respectively. Thus, FCM detection of viral antigens offers a potentially useful automated assay for the clinical diagnosis of multiple blood-borne viruses.…”
Section: Cd38mentioning
confidence: 99%
“…The aim of the present study was to investigate prospectively the early events in PBMc following experimental infection of woodchucks. Since WHV and HBV infections of PBMC are characterized by low levels of viral DNA/RNA and antigens [5], two highly sensitive methods were used: flow cytometry [6,7] to detect WHV antigens on lymphocytes surface and PCR [8,9] to detect WHV DNA and RNA in both serum and PBMC.…”
Section: Introductionmentioning
confidence: 99%